Semi-automated modeling of combined stained glasses - Petrushevskyi, Andrii (Theory and practice of design, 2022)
The possibility of forming an algorithm that allows creating computer projects of stained glass paintings by a semi-automated tool is being investigated. The purpose. To form an algorithm of actions based on classical stained glass technology using specialized modeling tools to create a project for a combined stained glass canvas. Methodology. The following methods were used in the study: 1) analytical method by which the literature was analyzed; 2) theoretical and conceptual method, which allowed to determine the conditions necessary for the introduction of IT technology in cultural and artistic practice; The study used methods of computer modeling and analysis, which increased the accuracy of the results. Results. The basic tools and algorithm of their use necessary for creation of the professional project of a stained-glass cloth are developed. The scientificance novelty. It consists in creating a concept of new computer tools and an algorithm for their use, aimed at improving the quality of stained glass projects and speeding up the workflow. Practical significance. This algorithm and the tools mentioned in the article can be useful in creating computer software designed for the design of stained glass.